AMP-activated protein kinase promotes epithelial-mesenchymal transition in cancer cells through Twist1 upregulation - Saxena, Meera (J Cell Sci, 2018)
The developmental programme of epithelial-mesenchymal transition (EMT), involving loss of epithelial and acquisition of mesenchymal properties, plays an important role in the invasion-metastasis cascade of cancer cells. In the present study, we show that activation of AMP-activated protein kinase (AMPK) using A769662 led to a concomitant induction of EMT in multiple cancer cell types, as observed by enhanced expression of mesenchymal markers, decrease in epithelial markers, and increase in migration and invasion. In contrast, inhibition or depletion of AMPK led to a reversal of EMT. Importantly, AMPK activity was found to be necessary for the induction of EMT by physiological cues such as hypoxia and TGFβ treatment. Furthermore, AMPK activation increased the expression and nuclear localization of Twist1, an EMT transcription factor. Depletion of Twist1 impaired AMPK-induced EMT phenotypes, suggesting that AMPK might mediate its effects on EMT, at least in part, through Twist1 upregulation. Inhibition or depletion of AMPK also attenuated metastasis. Thus, our data underscore a central role for AMPK in the induction of EMT and in metastasis, suggesting that strategies targeting AMPK might provide novel approaches to curb cancer spread.